Transparent, methacrylate‐based polymer networks with controlled crosslinker ductility. Issue 3 (27th July 2020) - Masser, Kevin A.; Orlicki, Joshua A.; Napadensky, Eugene; Taylor, Terrence; Harris, Doug
Abstract: A series of transparent methacrylate‐based crosslinked polymer networks are prepared in which the crosslinker length is controlled as a means to investigate the effects of network ductility on mechanical and ballistic properties. In each network the optical clarity of pure poly(methyl methacrylate) (PMMA) is retained, as well as a low value of haze. Both the glass transition temperature ( T g ) and the tensile modulus of the networks are highly tunable, with network values both above and well below that of pure PMMA or the pure crosslinker network. The ballistic performance is likewise affected, with performance values of up to 400% greater than neat PMMA. We examine the effects of the crosslinker molecular weight on the impact performance, finding that, in these systems, the molecular weight between crosslinks is not a driving factor for the impact performance, and this may broadly translate to polymer networks in general. We find that improvements in ballistic performance can be realized at low molecular weight between crosslinks, provided the crosslinking agent is of sufficient ductility. Abstract :